Enhanced wastewater bioremediation by a sulfur-based copolymer as scaffold for microalgae immobilization (AlgaPol). (February 2023) - Leon-Vaz, Antonio; Cubero-Cardoso, Juan; Trujillo-Reyes, Ángeles; Fermoso, Fernando G.; León, Rosa; Funk, Christiane; Vigara, Javier; Urbano, Juan
Abstract: In recent years, there has been an increasing concern related to the contamination of aqueous ecosystems by heavy metals, highlighting the need to improve the current techniques for remediation. This work intends to address the problem of removing heavy metals from waterbodies by combining two complementary methodologies: adsorption to a copolymer synthesized by inverse vulcanization of sulfur and vegetable oils and phytoremediation by the microalga Chlorella sorokiniana to enhance the metal adsorption. After studying the tolerance and growth of Chlorella sorokiniana in the presence of the copolymer, the adsorption of highly concentrated Cd 2+ (50 mg L −1 ) by the copolymer and microalgae on their own and the combined immobilized system (AlgaPol) was compared. Additionally, adsorption studies have been performed on mixtures of the heavy metals Cd 2+ and Cu 2+ at a concentration of 8 mg L −1 each. AlgaPol biofilm is able to remove these metals from the growth medium by more than 90%. The excellent metal adsorption capacity of this biofilm can be kinetically described by a pseudo-second-order model. Graphical abstract: Image 1 Highlights: C. sorokiniana can tolerate the presence of S/CO copolymers. C. sorokiniana is able to use S/CO copolymers as support for immobilization. Biofilms of C. sorokiniana -S/CO copolymers are able to adsorb 50 mg L −1 of Cd 2+ . These biofilms also adsorb mixtures of the heavy metals Cu 2+ and Cd 2+ (8 mg L −1 ). Adsorption kinetics fit to a pseudo-second-order equation.